Body size perception in stroke patients with paresis. - Azam Shahvaroughi-Farahani (Public Library of Science (PLoS), 2021)
Recent studies have suggested that people's intent and ability to act also can influence their perception of their bodies' peripersonal space. Vice versa one could assume that the inability to reach toward and grasp an object might have an impact on the subject's perception of reaching distance. Here we tested this prediction by investigating body size and action capability perception of neurological patients suffering from arm paresis after stroke, comparing 32 right-brain-damaged patients (13 with left-sided arm paresis without additional spatial neglect, 10 with left-sided arm paresis and additional spatial neglect, 9 patients had neither arm paresis nor neglect) and 27 healthy controls. Nineteen of the group of right hemisphere stroke patients could be re-examined about five months after initial injury. Arm length was estimated in three different methodological approaches: explicit visual, explicit tactile/proprioceptive, and implicit reaching. Results fulfilled the working hypothesis. Patients with an arm paresis indeed perceived their bodies differently. We found a transient overestimation of the length of the contralesional, paretic arm after stroke. Body size and action capability perception for the extremities thus indeed seem to be tightly linked in humans.